Combination Therapy of Topical Antioxidant Gel and Platelet-Rich Plasma (PRP) in Pyoderma Gangrenosum Ulcer: A Case Report - Kamilah, Lian; Bobby Febrianto; Nurrachmat Mulianto; Nugrohoaji Dharmawan; Harijono Kariosentono (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Pyoderma gangrenosum (PG) is a rare necrotic ulcerative skin disease, often associated with an underlying systemic condition. Bacterial coinfection in PG can worsen the course of the disease and slow healing. Case presentation: We report the case of a 25-year-old woman with PG of her left leg complicated by Pseudomonas aeruginosa co-infection. The patient had a history of poorly treated psoriasis. The diagnosis is made based on disease history, physical examination, microbiological examination, and histopathological examination. The patient was treated with oral levofloxacin and topical combination therapy of astaxanthin and platelet-rich plasma (PRP) with wound debridement. Significant clinical improvement was achieved within six weeks. Conclusion: PG with bacterial coinfection requires appropriate diagnosis and treatment to achieve optimal results. Topical therapy combining astaxanthin and PRP with wound debridement proved effective in this case.